2016
DOI: 10.3126/saarctb.v12i1.15935
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Knowledge of Pulmonary Tuberculosis and DOTS among Pulmonary Tuberculosis Patients in West Tripura District, India

Abstract: Introduction: A study was conducted for six randomly selected designated Microscopy Centre areas of West Tripura District of India with objectives to assess the knowledge regarding Pulmonary Tuberculosis (PTB) and DOTS among the PTB patients and to identify the factors determining the knowledge.Methodology: This cross-sectional study was conducted among 220 PTB patients registered for treatment with DOTS therapy during July 2011 to June 2012.Results: The study showed that 29.10% of the patients had satisfactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 5 publications
1
17
2
Order By: Relevance
“…While discussing the rout of transmission of TB, 55.6% of the respondents in the current study declared that TB is transmitted by droplets, these findings are consistent with earlier studies reported in literature. [17][18][19][20][21][22] However, contrary to our findings, respondents from other studies [23][24][25][26][27] reported poor knowledge about the transmission of TB. When the study participants were asked about eating together with family, 60% of respondents have a positive response; these findings were not in agreement with Malaysian study [23] where only 40% of respondents have positive response.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…While discussing the rout of transmission of TB, 55.6% of the respondents in the current study declared that TB is transmitted by droplets, these findings are consistent with earlier studies reported in literature. [17][18][19][20][21][22] However, contrary to our findings, respondents from other studies [23][24][25][26][27] reported poor knowledge about the transmission of TB. When the study participants were asked about eating together with family, 60% of respondents have a positive response; these findings were not in agreement with Malaysian study [23] where only 40% of respondents have positive response.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding was supported by other studies. [17,19,[20][21]23] However, these finding were not in line with other studies reported in literature. [24,27,28] Our study findings showed a significant difference in median scores for gender, age, education, marital, living status, stigma and health education.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…On the question of communicability of TB, 78.4% of our patients knew that it was a communicable disease. Das et al .,[5] Vidhani et al . [6] from Gujarat, Jangid et al .…”
Section: Discussionmentioning
confidence: 99%
“…So far, various investigators from different parts of India[5678910111213] and outside India[1415161718] had measured the level of awareness and knowledge of TB patients about TB. However, no such information is available from Uttarakhand State where the estimates of incidence of TB cases are higher than the national estimates.…”
Section: Introductionmentioning
confidence: 99%